2003
DOI: 10.1093/humrep/deg428
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification of zona-free rabbit expanded or hatching blastocysts: a possible model for human blastocysts

Abstract: These result demonstrate that denuded expanded or hatching rabbit blastocysts of greater size can be satisfactorily vitrified by use of a two-step procedure. The similarity of vitrification solutions used in humans could make it feasible to test such a procedure on human denuded blastocysts of different sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…In vivo-produced mouse morulae that were cultured till the embryos hatched through the zona pellucida and then vitrified achieved a survival rate of 77% (79/103) after warming (Zhu et al 1996). Denuded (by acidic treatment) and then vitrified rabbit blastocysts resulted in 91% survival after warming (Cervera & Garcia-Ximenez 2003). When assisted hatching, using diode laser, was conducted before freezing of human blastocysts, 75.4% post-thaw survival and 31.4% clinical pregnancies were achieved (Kung et al 2003).…”
Section: Manipulations To the Zona Pellucidamentioning
confidence: 99%
“…In vivo-produced mouse morulae that were cultured till the embryos hatched through the zona pellucida and then vitrified achieved a survival rate of 77% (79/103) after warming (Zhu et al 1996). Denuded (by acidic treatment) and then vitrified rabbit blastocysts resulted in 91% survival after warming (Cervera & Garcia-Ximenez 2003). When assisted hatching, using diode laser, was conducted before freezing of human blastocysts, 75.4% post-thaw survival and 31.4% clinical pregnancies were achieved (Kung et al 2003).…”
Section: Manipulations To the Zona Pellucidamentioning
confidence: 99%
“…In this way, the damage we observed in zona-free vitrified blastomeres might have been caused by osmotic stress that occurred during the addition and removal of concentrated cryoprotective solutions (11)(12)(13)(14) or during the removal of excess vitrification solution (VS) before cooling. The cryotop method involves the removal of the majority of the VS so that only a thin layer covers the biologic sample (7,8).…”
mentioning
confidence: 99%
“…These can be classified into two main categories: [1] hatching of the ZP performed by either laser, acidified Tyrode's solution, repeated micropipetting, or spontaneously by extending the culture of expanding blastocysts (12)(13)(14)(15)(16), and [2] blastocele collapse, passively by puncture or actively by microsuction (11,(17)(18)(19). Clinical trials adopting these techniques have shown significant improvement in terms of survival, fertilization, and pregnancy rates (15,(17)(18)(19).…”
mentioning
confidence: 99%